MODEL SISTEM PARKIR DENGAN MIKROKONTROLER (A MICROCONTROLER BASED PARKING SYSTEM MODEL) - Hendro Joko Prasetiyo; Fajar Budi Hartono; Aryati Wuryandari (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2022)
Recently, many cars in big cities are common things. The quantity of cars becomes a new problem, such as car parking, mainly in a crowded shopping centre. People that look for parking ground may often find some problems, for example they often find that the parking area is currently full after long queue time to enter parking. Based on this problem, has been constructed a Modelling of Computer-Based Parking Area Management System. This system is made to solve parking problem, particularly in shopping centre. The modelling is based around ATMEL MCS-51 Microcontroller. It works by counting the number of cars entering the parking centre. The system will search for an empty space in the parking area. After the consumers get an exact information about their car parking location, parking ticket will be printed out automatically. Finally, computer will count and print the parking fee before cars leave the parking area. The conclusion of this modelling device is that it is to print tickets automatically and can locate the position or the place of parking lot that are still available.